Cortinarius khinganensis (Agaricales), a new species of section Illumini from Northeast China - Xie, Meng-Le; Wei, Tie-Zheng; Dima, Bálint; Fu, Yong-Ping; Ji, Rui-Qing; Li, Yu (Phytotaxa, 2021)
This study presents one telamonioid species new to science based on morphological characteristics and molecular phylogenetic analyses. Cortinarius khinganensis was collected from the Greater Khingan Mountains, Northeast China and it is characterized by hygrophanous, vivid brownish red and striate pileus, white universal veil, and subglobose spores. According to phylogenetic analyses results, C. khinganensis belongs to the section Illumini, which is a lineage distantly related from subgenus Telamonia sensu stricto. Detailed descriptions of the new species and the comparisons with morphologically similar species are provided. The phylogenetic relationships within the section Illumini are also discussed.